The Development of Learning Media Based on Islamic Comics in Natural Sciences Force and Motion Material - Irfa'i Alfian Mubaidilla; Ziana Dhurrotul Ainiyah (Universitas Muhammadiyah Sidoarjo, 2022)
This research and development aims to increase the effectiveness of learning in class IV SD Muhammadiyah 9 Malang. The development of Islamic comic-based learning media aims to (1) produce learning media products by describing the media development process, (2) describe the level of feasibility of learning media, and (3) describe the level of effectiveness of learning media in the science material subject force and motion of Muhammadiyah 9